Study of Activated Carbon from Coconut Shell Waste to Adsorb Cu and Mn Metals in Acid Mine Drainage - Lailan Ni`mah; Mahfud Mahfud; Sri Rachmania Juliastuti (Journal of Fibers and Polymer Composites, 2022)
Abstract. The purpose of this research is to make activated carbon from coconut shell carbon and examine its use in adsorbing metals in acid mine drainage; to study the types of activators; to determine the optimum mass for the efficiency of reducing the concentration of Cu2+ metal and Mn2+ metal (percent removal) using the activated carbon from coconut shell carbon; and to determine the adsorption of isothermal model. Based on the results of the study, it is concluded that activated carbon could be made from coconut shell carbon with 20% H3PO4 chemical activation. Before being activated, it was made by heating at a temperature of 300°C for 2 hours. The best activated carbon in terms of metals adsorption in acid mine drainage was in a mass of 4 grams with each percent removal of 57.62% for Cu metal and 91.37% for Mn metal. Data analysis of the effect of concentration on adsorption capacity used the Langmuir and Freundlich isotherm equations. The Langmuir equation for the adsorption of Mn metal obtained the maximum adsorption capacity (qmax) of 15.16 mg/g; KL=73.09 mol/L and R2=0.9568. Meanwhile, the adsorption of Cu metal obtained the maximum adsorption capacity (qmax)=4.73 mg/g; KL=73.14 mol/L and R2= 0.9304. In Freundlich's equation, on the adsorption of Mn metal, the resulting KF=15.14 mol/L; R2=0.9129, while on the adsorption of Cu metal, the resulting KF=.72 mol/L; R2= 0.9092. Based on the data, the adsorption isotherm curve more closely follows the Langmuir isotherm model (adsorption takes place in one layer (monolayer).